Sami tourism in destination development: conflict and collaboration. (2nd July 2016) - Olsen, Lise Smed
ABSTRACT: Indigenous tourism has become an important component of the tourism industry. Previous indigenous tourism research has indicated three conflict areas that can have an impact on destination development: internal conflicts over indigenous identity, the use of indigenous culture in destination marketing, and land-use conflicts. To varying degrees these areas of conflict have been found to impact local and regional destination development in northern Europe. This paper draws on case studies to understand how conflicts in Sami tourism in local and regional destination development are addressed through stakeholder collaboration in Jokkmokk, Sweden and Kautokeino, Norway. The study indicates that collaboration between destination marketing organizations and Sami stakeholders has been initiated and has improved destination marketing. Conflicts relating to indigenous identity and land-use are more challenging to address through collaboration due to the history of colonization by nation states. Such prevailing conflicts place certain requirements on the facilitator of collaboration processes in tourism destination development.